(untitled) (Al-Mansour Journal, 2022)
Play the Process of money laundering and bleaching of money a serious role on the national economy and its impact on the social level , because the corruption baraknet investment and financial management has severely damaged economically, politically and socially . Accordingly, it is their national duty is to work to eradicate corruption in all possible means to achieve decent citizen of the necessities of life all the happy kind . Therefore, we will address corruption in all its tedious detail in this research we hope to achieve the desired goals.